A New Wave of "Space Nationalism" in the United States: Why Are Evangelicals Good With It?. (February 2023) - Molle, Andrea
Abstract: Despite evidence that shows how the support for space programs correlates with liberal political views and a lower level of religiosity, recent data suggest that more conservative positions may have an even more substantial effect under the appropriate conditions. Using the available data from Pew's American Trends Panel, we seek to clarify this interactional effect of political and religious preferences on the level of interest in the space programs and commitment to space politics support among Evangelicals as it changed during Trump's presidency. Our research hypothesizes that during this time, the simultaneous presence of nationalist views in both accounts of politics and religion may be linked to the underlying concept of "space nationalism, " that is, the belief that the United States should lead in space exploration, resulting in an increased level of support for space programs. This article presents the results of several iterations of linear regression models. Controlling for robust sociodemographic variables, our findings show a statistically significant effect of nationalist views and religious beliefs. Our results confirm that a combination of nationalism and religious views is a robust predictor of Evangelicals' space exploration support.